ANALISIS MOTIF, ALASAN UMUM DAN MODEL PENGGUNAAN PIDANA MATI TERHADAP TERPIDANA NARKOTIKA DI INDONESIA - Zainab Ompu Jainah (KEADILAN PROGRESIF, 2019)
Regarding the imposition of capital punishment on criminals in Indonesia in the perspective of human rights based on the 1945 Constitution it turns out that it does not violate theprovisions of human rights law. The main problem is the object of research, namely how theimposition of capital punishment on perpetrators of criminal acts in criminal justice practicesin Indonesia. This research is a normative legal research through a statutory approach,conceptual data used secondary data by conducting library studies and data analysis carriedout by qualitative analysis. The results of the study show that the imposition of capitalpunishment on narcotics and psychotropic offenders in criminal justice practices inIndonesia, the application of narcotics and psychotropic offenders does not violate humanrights because it does not conflict with the provisions of Article 28A, Article 28I paragraph(1) and Article 28J paragraph ( 2) The 1945 Constitution and does not violate Indonesia'sinternational legal obligations born of international agreements concerning the eradicationof illicit trafficking in narcotics and psychotropic drugs so that law enforcement needs to beimproved.